Overview of Risk Factors for Ectopic Pregnancy at Dr. M. Djamil General Hospital, Padang, Indonesia - Rozali, Azwar; Asnawi, Zainuddin (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Ectopic pregnancy is an emergency condition that is the cause of maternal death during the first trimester of pregnancy. Most extrauterine implantations occur in the fallopian tubes. This study aimed to find an overview factor risk of ectopic pregnancy at Dr. M Djamil General Hospital, Padang, Indonesia. Methods: This study was a descriptive observational study and used secondary data from medical record data at the medical record installation of Dr. M Djamil General Hospital, Padang, Indonesia. A total of 100 research subjects participated in this study, and the research subjects met the inclusion criteria. The inclusion criteria in this study were patients with ectopic pregnancy disorders who were treated at Dr. M Djamil General Hospital, Padang, Indonesia, over 18 years of age and had complete medical record data. Data analysis was carried out using SPSS software version 25. Univariate analysis was performed to present the distribution frequency data for each variable test. Results: The majority of research subjects had an age range of 26-35 years (55%). The most common risk factors in this study were a history of abortion in a previous pregnancy (47%), parity 0 (46%), and abortion occurring in the first pregnancy (35%). Conclusion: Maternal age, history of abortion, parity, and gravidity are risk factors that play a role in the incidence of ectopic pregnancy at Dr. M Djamil General Hospital, Padang, Indonesia.